Development of New Treatments for Asthma and Neuropathic Pain Based on Ɣ-Aminobutyric Acid a Receptor (GABAAR) Ligands - (:unkn) unknown (My University, 2022)
The γ-aminobutyric acid A receptor (GABAAR) is a ligand-gated pentameric chloride channel consisting of several identified subunits: α1-6, β1-3, γ1-3, δ, ε, π, θ, ρ1-3.1-2 Typical arrangement of subunits consists of two α subunits, two β subunits, and one γ subunit.3 GABAARs have two binding sites for the endogenous ligand γ-aminobutyric acid (GABA), between the α and β subunits. GABAARs also have a binding site for positive allosteric modulators, such as benzodiazepines, between the α and γ subunits.4-5 Due to their ability to treat anxiety, epilepsy, insomnia, and muscle relaxation, benzodiazepines are widely prescribed pharmaceuticals.6-7 Still, adverse effects result from benzodiazepine use, including but not limited to: sedation, impaired motor coordination, amnesia, tolerance, dependence, and severe withdrawal symptoms.6, 8 Selectivity of benzodiazepines to specific GABAAR subtypes is currently well accepted drug discovery strategy.8 The rotarod assay has been used for over 70 years to quantify the neurological effects of muscle relaxants, convulsants, and central nervous system (CNS) depressants.12 It is a reliable and sensitive in vivo sensorimotor assay that can detect neurological deficits such as sedation or impaired motor coordination.¹² Additionally, an open field test can be performed in parallel to provide a more robust analysis of neurological deficits. The Arnold Group has used these assays to screen hundreds of novel subtype-selective imidazodiazepines to identify those without adverse CNS effects. Imidazodiazepines demonstrating no adverse CNS effects were used to develop leads to treat asthma inflammation and neuropathic pain by targeting non-neuronal cells expressing a narrow subset of GABAAR subunits. 9-11 T-lymphocytes, alveolar macrophages, and eosinophils¹⁷ all have been shown to express functional GABAARs suggesting their role in the airway inflammatory response.13⁻15 CD4+ T-lymphocytes are of significant interest for their role in stimulating and coordinating the airway inflammatory immune response.14 Here, we describe the relationship between imidazodiazepines targeting non-neuronal immune cells and the corresponding airway inflammatory response both in vivo and in vitro. Airway hyperresponsiveness (AHR) was investigated in methacholine-challenged murine models in vivo using a non-invasive airway mechanics (NAM) plethysmograph. Methacholine, a cholinergic drug, acts on muscarinic receptors and causes narrowing of airways similar to asthma.¹⁶ The NAM instrument measures pressure, volume, and frequency of respiration and combines these parameters into an sRaw value measured in cmH2O*sec. Several novel imidazodiazepines were identified to have lower sRaw values in this model compared to commercially available asthma therapeutics. This trend was observed in studies of repeat dose and prophylactic dose for orally and nebulized delivered compounds, as well as for rescue inhalant studies. Lead compounds were also subject to in vitro experimentation. CD4+ T-cells have a well understood role in asthma and are responsible for perpetuating the inflammatory response by infiltrating airways and secreting inflammatory cytokines.¹⁸ The cytokine release directs other cell types to mediate many of the clinical characteristics of asthma, including heightened IgE production, increased eosinophilia, and accelerated immune cell proliferation.¹⁹ This complex inflammatory reaction can be classified into Th1 or Th2 responses. Th1 responses are characterized by cytokines like interferon γ (IFNγ), interleukin-2 (IL-2), and lymphotoxin (LT), which promote the cell-mediated immune response.²⁰ The Th2 immune response is characterized by production of multiple cytokines: IL-4, IL-5, IL-10, and IL-13, among others.²⁰ To investigate the anti-inflammatory effects of GABAAR ligands, a protocol was developed to quantify the reduction of IL-5 and IL-13 production by primary activated CD4+ T-cells isolated from female Swiss Webster splenocytes using rtPCR. Functional γ-aminobutyric acid type A receptors (GABAARs) are well-characterized in neurons and have been discovered on glial cells. This includes α1, α3, and β1 subunits found on mouse microglia,²¹ which have been reported to mediate immune signaling.²² Previous anti-inflammatory studies with novel α2/α3-subtype GABAAR positive allosteric modulators have shown analgesic properties.²⁵,²⁶ Taken together, these results suggest that novel imidazodiazepines are neuropathic pain lead compounds, reducing inflammation through targeting CNS microglia, and providing an analgesic effect. A murine formalin test was performed to investigate in vivo compound efficacy in reducing neuropathic pain.
Keywords: Asthma; Biochemistry; GABA A Receptor; Immunology; MIDD0301; Neuropathic Pain